Analysis of Determinants of Corporate Cash Holdings - Examples from Companies in Serbia - Račić, Željko; Stanišić, Nemanja (The European Journal of Applied Economics, 2017)
In this study, we aimed to analyse the empirical determinants of cash holdings on the sample of nonfinancial companies operating in the Republic of Serbia. For that purpose, dynamic panel data models were estimated by utilising the generalised method of moments for the period from 2008 to 2013. The econometric analysis indicates that companies with higher cash flow hold more cash in their assets. Larger companies as well as companies with more liquid assets and higher turnover coefficients tend to reduce their cash levels. According to the results, companies operating in the Republic of Serbia tend to hold the optimal level of cash and prefer internal sources of financing, which is in line with the principles of trade-off theory and pecking order theory.